THE EFFECT OF SELF-CAPITAL, LOAN CAPITAL, WORKING CAPITAL, TOTAL ASSET AND BUSINESS VOLUME ON INCOME THE REST OF BUSINESS RESULTS (A Case Study on the Cooperative Employees of the Republic of Indonesia Guru Kampar Air Tiris District 2009-2018) - Alvin Ridho; Arman Arman; Mustafa Kamal (Jurnal Riset Manajemen Indonesia, 2020)
This study aims to determine the effect of own capital, loan capital, working capital, total asset and business volume on the remaining business results at the Koperasi Pegawai Republik Indonesia Guru, Kampar Air Tiris District 2009-2018. The population in this study were all financial reports of the Koperasi Pegawai Republik Indonesia Guru, Kampar Air Tiris District 2009-2018. Methods of data collection by observation, research files and interviews. The data analysis techniques used include: descriptive analysis, normality test, classical assumption test, multicollinearity test, heteroscedasticity test, autocorrelation test. Hypothesis testing uses multiple linear regression analysis. The results showed that simultaneously own capital, loan capital, working capital, total assets and business volume had a significant effect on the residual income (SHU) with a significance value of 0.011. Partially working capital has a significant effect on SHU with a significance value of 0.035.